Exploration of Alternative CantingCap with LidiMaterials in Contemporary Batik Production - Ayu, Dewita Sekar; Fardhani, Ahda Yunia Sekar (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Batik, a cherished heritage of the archipelago, holds significant artistic value. This research endeavors to introduce novel innovations in the tools employed in contemporary batik production. Several advancements have been made in batik-making tools, notably the utilization of sticks as a substitute for writing canting. This discovery presents an opportunity to employ sticks as an alternative to canting cap tools in contemporary batik production. The accessibility and cost-effectiveness of sticks compared to copper canting caps make this alternative a viable option. The research methodology employed is a descriptive qualitative approach, utilizing data collection techniques such as literature review, observation, interviews, and exploration. The creative process involved three stages: initial exploration, which aimed to identify the optimal stick type and visual form by comparing the strokes produced by canting with small and thick sticks; further exploration, which involved utilizing sticks as alternative batik canting tools by arranging sticks on clay based on the motifs obtained in the initial exploration; and final exploration, which utilized the glass comparison technique to refine the composition. The outcomes of this research provide an alternative tool made of stick material and fabric sheets, derived from the exploration of contemporary batik motifs using alternative tools to replace canting caps with stick material.